1999
DOI: 10.1152/ajpheart.1999.277.4.h1600
|View full text |Cite
|
Sign up to set email alerts
|

Impaired wound healing and angiogenesis in eNOS-deficient mice

Abstract: A role for nitric oxide (NO) in wound healing has been proposed; however, the absolute requirement of NO for wound healing in vivo and the contribution of endothelial NO synthase (eNOS) have not been determined. Experiments were carried out using eNOS gene knockout (KO) mice to determine the requirement for eNOS on wound closure and wound strength. Excisional wound closure was significantly delayed in the eNOS KO mice (29.4 +/- 2.2 days) compared with wild-type (WT) controls (20.2 +/- 0.4 days). At 10 days, in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

12
247
2
6

Year Published

2001
2001
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 272 publications
(267 citation statements)
references
References 25 publications
12
247
2
6
Order By: Relevance
“…23 Murohara et al 4 reported that angiogenesis in response to tissue ischemia or VEGF administration was significantly impaired in eNOS-deficient mice. An angiogenesis-promoting role for EC-derived NO was also suggested in the report by Lee et al, 21 who showed impaired wound healing and angiogenesis in eNOS-deficient mice. We observed that there was a marked reduction in the number of infiltrating capillaries containing red blood cells within Matrigel plugs taken from L-NAME-treated mice compared with untreated mice.…”
Section: Rikitake Et Alsupporting
confidence: 56%
See 2 more Smart Citations
“…23 Murohara et al 4 reported that angiogenesis in response to tissue ischemia or VEGF administration was significantly impaired in eNOS-deficient mice. An angiogenesis-promoting role for EC-derived NO was also suggested in the report by Lee et al, 21 who showed impaired wound healing and angiogenesis in eNOS-deficient mice. We observed that there was a marked reduction in the number of infiltrating capillaries containing red blood cells within Matrigel plugs taken from L-NAME-treated mice compared with untreated mice.…”
Section: Rikitake Et Alsupporting
confidence: 56%
“…Interestingly, previous studies have demonstrated the crucial role of NO in wound healing, as wound healing is accelerated by systemic administration of L-arginine, a substrate of NOS, but delayed by NOS inhibitors. 19,20 Lee et al 21 reported impaired wound healing and angiogenesis in eNOS-deficient mice. Together with those findings, our data demonstrating NO-dependent angiogenesis by S1P may account for the critical role of NO in wound repair.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…The integrity of the endothelium therefore bears an enormous significance in physiological processese.g. wound healing after an injury to the vascular wall -where controlled proliferation and migration of endothelial cells are required [2]. However, several pathological conditions including coronary atherosclerosis, a major cause of morbidity and mortality in the Western World, are associated with an uncontrolled as well as accelerated proliferation and migration of both endothelial and VSMCs [5].…”
Section: Discussionmentioning
confidence: 99%
“…The integrity of the endothelial layer is preserved by controlled proliferation and migration of endothelial cells in a number of physiological processes such as angiogenesis and during wound healing after an injury to the vascular wall [2,3]. However, in several pathological conditions e.g.…”
Section: Introductionmentioning
confidence: 99%